Economic Implications of Further Harmonisation of Electronic Communications Regulation in the EU - J. Scott Marcus; Christian Wernick (Intereconomics, 2017)
There are some aspects of the European RFEC and its implementation today that could benefit from increased harmonisation; there are others in which substantial accommodation to local, national or regional circumstances and preferences is desirable or required.
Keywords: 330